1968
DOI: 10.1007/bf00387615
|View full text |Cite
|
Sign up to set email alerts
|

Auxin transport in roots

Abstract: The dependence upon metabolism of the acropetal polar flux of IAA through 6-mm Zea root segments has been investigated using IAA-I-(14)C.The results are as follows: 1. At 0°C the acropetal movement of IAA is reduced to the level of basipetal movement and the polar flux is thus abolished, even after transport periods of 24 hours. 2. In dead tissue the acropetal polar flux is abolished and replaced by a basipetal polar flux. 3. On exposing segments to anaerobic conditions, the acropetal polar flux of IAA is seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The movement of auxins in plant root is generally in an acropetal direction (Wilkins and Scott, 1968). However, a study conducted in our laboratory revealed that addition of radiolabeled 3'-14 C-IAA to aseptic sterile soil and nonsterile soil resulted in assimilation and translocation of the label to the shoot tissues as amino acid conjugates of IAA .…”
Section: Between [N] In the Plant Tissues And Log[l-trp] Excluding Thmentioning
confidence: 99%
“…The movement of auxins in plant root is generally in an acropetal direction (Wilkins and Scott, 1968). However, a study conducted in our laboratory revealed that addition of radiolabeled 3'-14 C-IAA to aseptic sterile soil and nonsterile soil resulted in assimilation and translocation of the label to the shoot tissues as amino acid conjugates of IAA .…”
Section: Between [N] In the Plant Tissues And Log[l-trp] Excluding Thmentioning
confidence: 99%